A hipótese de ação rescisória do Art. 525, §15 do Código de Processo Civil, sob a ótica do sistema brasileiro de precedentes judiciais - Moro, Lais Martins (2022)
This essay deals with setting aside proceedings set forth in §15 of s. 525 of the Code of Civil Procedure and its implications, in particular considering the notion of legal certainty introduced by the Brazilian system of precedents. Firstly, this text analysis the emphasis given by the current Civil Procedural Law to case law uniformity, which prioritises legal certainty and also an isonomic method to guarantee individuals’ rights through a system of precedents. Secondly, this essay carries out a more in-depth analysis of the principle of legal certainty, enshrined in the legal concept of res judicata. The general aspects of res judicata as well as its legal nature, classification, limits, and methods of disregard, are dissected on the following pages. Well established the premises, this essay examines setting aside proceedings based on §15 of s. 525 of the Code of Civil Procedure, i.e., when the unenforceability of a court order for debt arises from a decision of unconstitutionality handed down by the Brazilian Supreme Court through diffuse or concentrated judicial review. The essay discusses the notion of unconstitutionality and its correspondent remedy of judicial review. In this context, the text weights up the weaknesses and strengths of a system of precedents, given this new possibility of disregard of res judicata, mostly due to the lengthening of the time period to file setting aside proceedings. At the end, this essay discussed the issue whether would exist any incompatibility between, on the one side, this new possibility of setting aside proceedings and, on the other side, the desired isonomy among individuals. This potential clash is assessed considering legal concepts like case law uniformity, legal certainty, predictability, and the dynamics of each society